Plan de mejoramiento de la gestión del talento humano en la rotación de personal en la empresa maquinados ltda en Duitama. (2021)
This thesis is practically given by the need to improve the personnel recruitment process, the objective of this work is based on carrying out an improvement plan for the company Metalmecánica Ltda. In the city of Duitama, it is a proposal designed to minimize the index rotation of staff and that the company has an idea of how to carry out this process with quality. The company Metalmecánica Ltda. Has a problem that for the current year its turnover rate rose significantly, leading to high costs of hiring new personnel and a deficit in the financial area, since that budget can be used for another purpose, not they execute a complete process for said activity and for this reason this extra cost is generated. The topics to be discussed were investigated, such as staff selection, staff rotation, PHVA cycle, Human talent management, to obtain more knowledge when developing specific objectives, the methodology was carried out based on information provided from the company, and what I learned in the course of my career I applied in this project. It is desired to obtain satisfactory results with the strategies that were implemented, new processes were exposed for the recruitment of personnel, in addition to this, some formats are delivered so that when the company needs to link a new worker they are applied, and qualified personnel are hired and minimize that current 9% turnover rate.